National Crime Surveys: Redesign Data: Peoria Record Check Study - Groves, Robert M. ([Verlag nicht ermittelbar], 1987)
The purpose of this study was to measure criminal activity in the United States based on survey reports of crime victims. In the study two different questionnaire forms were used in order to assess which provided better responses. One form was very lengthy and asked detailed questions about each household, person, and incident. The second form was much shorter and asked very generalized questions. The data collection was an attempt to find alternative methods of sampling, interviewing, designing questionnaires, managing data, and reporting results. Detailed information is provided on household characteristics and other characteristics of the respondents, as well as on crime incidents, including burglary, vandalism, assault, and rape.